2H-Tetrakis(3,5-di-tert-butyl)phenylporphyrin on a Cu(110) Surface: Room-Temperature Self-Metalation and Surface-Reconstruction-Facilitated Self-Assembly - Zhang, Liang; Lepper, Michael; Stark, Michael Werner; Schuster, Ralf; Lungerich, Dominik; Jux, Norbert; Steinrück, Hans-Peter; Marbach, Hubertus (Chemistry - A European Journal, 2016)
The adsorption behavior of 2H-tetrakis(3,5-di-tert-butyl)phenylporphyrin (2HTTBPP) on Cu(110) and Cu(110)-(2x1)O surfaces have been investigated by using variable-temperature scanning tunneling microscopy (STM) under ultrahigh vacuum conditions. On the bare Cu(110) surface, individual 2HTTBPP molecules are observed. These molecules are immobilized on the surface with a particular orientation with respect to the crystallographic directions of the Cu(110) surface and do not form supramolecular aggregates up to full monolayer coverage. In contrast, a chiral supramolecular structure is formed on the Cu(110)-(2x1)O surface, which is stabilized by van der Waals interactions between the tert-butyl groups of neighboring molecules. These findings are explained by weakened molecule-substrate interactions on the Cu(110)-(2x1)O surface relative to the bare Cu(110) surface. By comparison with the corresponding results of Cu-tetrakis(3,5-di-tert-butyl)phenylporphyrin (CuTTBPP) on Cu(110) and Cu(110)-(2x1)O surfaces, we find that the 2HTTBPP molecules can self-metalate on both surfaces with copper atoms from the substrate at room temperature (RT). The possible origins of the self-metalation reaction at RT are discussed. Finally, peculiar irreversible temperature-dependent switching of the intramolecular conformations of the investigated molecules on the Cu(110) surface was observed and interpreted.
Keywords: adsorption; porphyrinoids; scanning tunneling microscopy; self-assembly; surfaces and interfaces